8(2)=3(x+3)

Simple and best practice solution for 8(2)=3(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2)=3(x+3) equation:


Simplifying
8(2) = 3(x + 3)

Multiply 8 * 2
16 = 3(x + 3)

Reorder the terms:
16 = 3(3 + x)
16 = (3 * 3 + x * 3)
16 = (9 + 3x)

Solving
16 = 9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
16 + -3x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
16 + -3x = 9 + 0
16 + -3x = 9

Add '-16' to each side of the equation.
16 + -16 + -3x = 9 + -16

Combine like terms: 16 + -16 = 0
0 + -3x = 9 + -16
-3x = 9 + -16

Combine like terms: 9 + -16 = -7
-3x = -7

Divide each side by '-3'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| 8(x-3)=6x+11-5x | | 42+22x=180 | | 13x+9x-8+50=180 | | 5x+90=2x-15 | | (32x-7y)-(28x-11y)=0 | | 1.6h+72=4h-30 | | -30x^2+35x-10=0 | | -4.42x+.9=-9.070-0.432 | | 11x-10y=30 | | 60+.50(200)=1.30(200) | | 20x-9(3)=7 | | 19+[3x(7-3)]-2= | | .5(-4x-5)=7x-.5 | | 3x^3-3x^6-9x^3+5=0 | | 65-85=x | | (x-1)(2x)(x-4)=40 | | 5d-33=7.2 | | 32x=5x-14 | | r/3-4=3 | | 3x-(2x-1)=5x+1-4x | | 60+.50(100)=1.30(100) | | -5.26+.21x=19.94 | | 7cos(7x)=0 | | 16x^2-4x+5-(16x^2-8x)+1=0 | | -12x-11=-47 | | 7(-8x)= | | -4x=12-x^2 | | -z-9=3.4(2z+4.3) | | -5.26+.21x=15.74 | | 20x-16y=48 | | 24x-9=18x-1 | | 85-65=x |

Equations solver categories